Numerical Analysis of Hollow Cross Section Reinforced Concrete Beams Strengthened by Steel Fibers Under Pure Torsion - Mures, Jawad K.; Chkheiwer, Aqeel H.; Ahmed, Mazin A. (Basrah Journal for Engineering Sciences, 2021)
This numerical study aimed to investigate the torsional behaviour of hollow cross section reinforced concrete members strengthened with steel fibers (end hooked and corrugated), subjected to pure torsion. The numerical results were compared with experimental results and show good agreement. The experimental study was conducted on ten steel fiber reinforced concrete specimens with low longitudinal reinforcement ratio to investigate the torsional behavior under pure torsion. For this analysis, a computer program (ANSYS 18.2) was used. The brick elements 8-nodes (SOLID65) were used to concrete simulation, while the steel bars simulated as axial members (link 180). The steel fibre was represented theoretically by the stress-strain relationship. The theoretical results indicated that the adopted smeared crack model is capable of making relatively acceptable estimations of cracking and ultimate torsional capacity of the members.